Do entrance fees crowd out donations for public goods? Evidence from a protected area in Costa Rica. (June 2015) - Alpízar, Francisco; Martinsson, Peter; Nordén, Anna
Abstract In this paper, we investigate how different levels of entrance fees affect donations for a public good, a natural park. To explore this issue, we conducted a stated preference study focusing on visitors' preferences for donating money to raise funds for a protected area in Costa Rica given different entrance fee levels. The results reveal that there is incomplete crowding out of donations when establishing an entrance fee.